A Bibliometric Analysis of Digital Recruitment Research from 2004 to 2024 - Muta'al, Muhammad Rofi'ud; Muthohirin, Muthohirin (Jurnal Prajaiswara, 2024)
Introduction/Main Objectives: This article provides an overview of bibliometric analysis of digital recruitment over the past 20 years. Recruitment is an essential part of human resource management because it determines the quality of the human resources that will join an organization. Technological developments also cannot be separated from the Human Resource Management aspect, including recruitment, so it influences the recruitment process by adopting information technology capabilities. So far, no one has carried out a bibliometric analysis on the topic of digital recruitment, so this article can be a guide for future researchers if they want to conduct research related to digital recruitment. Research Methods: The database used in this article is a database originating from Scopus, taking samples from 2004 to 2024 with a total of 149 documents. The application used to analyze and visualize data is VOSviewe with bibliographic coupling analysis, keyword co-occurrence, and temporal analysis. Finding/Results: Based on the analysis, the focus areas of this bibliometric analysis include 1) the application of human resource management, 2) the application of tools in Digital Recruitment, 3) processes involved in Digital Recruitment, and 4) Digital Recruitment in the medical health sector. Current themes emerging in this research include artificial intelligence, algorithms, recommender systems, and collaborative filtering, indicating new and relatively unexplored areas that could benefit from further investigation. Lastly, artificial intelligence and big data are increasingly shaping the future of human resource management, providing promising opportunities for future studies in Digital Recruiting.